Invitations, Incentives, and Conditions : A Randomized Evaluation of Demand-Side Interventions for Health Screenings - de Walque, Damien; Chukwuma, Adanna; Ayivi-Guedehoussou, Nono; Koshkakaryan, Marianna (Elsevier, 2022)
This randomized controlled trial investigates the impact of four demand-side interventions on health screening for diabetes and hypertension among Armenian adults. The interventions are 1) personalized invitations from a physician, 2) personalized invitations with information about peer screening behavior, 3) personalized invitations with a labeled but unconditional financial incentive, and 4) personal invitations with a conditional financial incentive. Compared with the control group, interventions 1 to 3 led to a significant increase in the screening rate of about 15 percentage points for diabetes and hypertension. The highest impact was measured for intervention 4 leading to a 31.2 percentage point increase in both screenings.